Plastic film and foil web handling guide - Hawkins, William E. (CRC Press LLC, 2011)
Written to assist anyone who works with webs directly or indirectly, The Plastic Film and Foil Web Handling Guide is a handbook for diagnosing and correcting problems with web handling technology. Covering web handling fundamentals, process-related technologies, troubleshooting, and solutions, it includes sufficient technical information to identify and correct defects in rolls (of film or foil). Readers will appreciate this unbiased look at web handling that also serves as a counterpoint to information from equipment suppliers.The text presents guidelines on:Roller alignment in machinesTensioning of websUse of web spreading and guiding devicesUse of razor slittersShear knife slittersEdge trim removalTrim disposalManagement of electrostatic charges on websWaste storage equipmentWinding technology is presented that addresses gage variation issues, cores and mandrels, vibration, speed issues, web thickness issues, web strength issues, coated web issues, laminated web issues, clear film issues, winding tension profile issues, and lay-on roller issues. A guide for troubleshooting web-handling problems and a glossary of terms for quick reference is also provided.